Propostas de melhorias para o processo de dobra em uma indústria metal-mecânica - Patitucci, Eduardo Jarnicki (2013)
The purpose of this study was to analyse the case in a metalmechanical indutry, seeking improvement for the bending process. This is a research-action, in which the author has participated in the analysis and in the deploymet of tools which are presented in this work. Firstly, the current scenario of bending sector will be analysed in order to point out the needs and the oportunities for the enhancement of the company, which is the aim of this study. Following, a theorical analysis was made regarding to Lean Manufacturing and Industrial Management tools. Among the countless tools mentioned by the specifc literature, the author chose those ones, which were more relevant and effective to solve the problems highlighted in the first scenario analysis. The third step consists of defining indicators. The main indicator used in this study was OEE, which allows to notice the different points of enhancement, as well as to evaluate the process improvements properly. The research was made “in loco” and the measures proposed were introduced to the company effectively, so that the improvements of bending process which occurred could be evaluated.